Environmental accounting in public sector: systematic literature review - Rahmawati, Evi; Nazaruddin, Ietje; Widiastuti, Harjanti; Sofyani, Hafiez; Kholid, Arif Wahyu Nur (Journal of Accounting and Investment, 2024)
Research aims: The literature on Environmental Accounting (EA) in the public sector is scarce, unlike in the private sector. Hence, this study aims to ascertain the trajectory of EA research in the public sector and extract insights from prior research on EA in the public sector.Design/Methodology/Approach: The research process was conducted in several stages following Anggraini et al. (2022) and Poje et al. (2022) with several modifications. The keywords were used to discover the articles relating to the topic, namely: “Environmental Reporting,” “Environmental Management,” or “Environmental Accounting,” “Green Accounting,” and “Public Sector”. The study employed an extended period, namely papers published in 2010-2023 in the database Scopus.com. Based on the specified criteria, the final paper that could be analyzed was 69 out of 112 articles.Research findings: Using VOS-viewer, 15 items of keyword themes were discovered. Then, the 15 items were classified into three clusters: Green Accounting, Environmental Regulation, and Sustainable Development Goals in the Public Sector. Theoretical contribution/Originality: The authors are unaware of any existing literature review research on EA, specifically in the public sector, even though it arises from environmental management accounting in the public sector. This study also demonstrates the inferences that can be derived.